Persepsi Siswa terhadap Peningkatan Kemampuan Membaca melalui Pendekatan Literasi Sekolah di SMP Negeri 1 MAPPAKASUNGGU - Ainun Mardia; Al Amira Amir; Dian Safitri; Balak Daeng (Politeknik Kampar, 2025)
This study aims to describe students’ perceptions of improving reading skills through the implementation of a school literacy approach at SMP Negeri 1 Mappakasunggu. Data were collected using questionnaire measuring students’ experiences, interests, and views regarding school literacy activities, including the use of a reading corner. The research employed a descriptive quantitative design. The findings indicate that the majority of students responded positively to the literacy activities conducted at the school. Students perceived that literacy programs—particularly the availability of a reading corner—helped enhance their interest in reading and improved their comprehension skills. These results reinforce that the school literacy approach can serve as an effective strategy for strengthening students’ reading abilities. The study recommends that schools continue to promote a robust literacy culture by providing adequate reading facilities, implementing daily reading habits, and fostering collaboration among teachers, students, and the school community.